The Use of Biomarkers in Early Diagnostics of Pancreatic Cancer - Kunovsky, Lumir; Tesarikova, Pavla; Kala, Zdenek; Kroupa, Radek; Kysela, Petr; Dolina, Jiri; Trna, Jan (Canadian journal of gastroenterology & hepatology, 2018)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal solid malignancies with increasing incidence. The poor prognosis is due to the aggressive nature of the tumor, late detection, and the resistance to chemotherapy and radiotherapy. A radical surgery procedure is the only treatment that has been shown to improve the 5-year survival rate to 20-25%. However, the majority of patients (80-85%) are diagnosed with locally advanced or metastatic disease and just 15-20% patients are diagnosed in an early stage allowing them to undergo the potentially curative surgical resection. The early detection of PDAC without the use of invasive methods is challenging and discovery of a cost-effective biomarker with high specificity and sensitivity could significantly improve the treatment and survival in these patients. In this review, we summarize current and newly examined biomarkers in early PDAC detection.
Keywords: Middle Aged; invazivní růst nádoru; nádory slinivky břišní; přežití bez známek nemoci; lidé středního věku; Carcinoma, Pancreatic Ductal; Adult; mužské pohlaví; Prognosis; Pancreatectomy; Risk Assessment; hodnocení rizik; dospělí; Humans; senioři; Survival Analysis; Neoplasm Staging; lidé; časná detekce nádoru; pankreatektomie; Neoplasm Invasiveness; Female; Disease-Free Survival; analýza přežití; Aged; Pancreatic Neoplasms; ženské pohlaví; Biomarkers, Tumor; Male; prognóza; Early Detection of Cancer; staging nádorů; nádorové biomarkery; duktální karcinom slinivky břišní